Hydroxyapatite carriers as drug eluting agents-An In Vitro analysis - Deepti Simon; K Ajith Kumar; Suresh Babu Sivadasan; Harikrishna Varma; Anita Balan (Wolters Kluwer Medknow Publications, 2020)
Introduction: Hydroxyapatite based drug carriers offer a customized alternative to the delivery of pharmacologic agents in the osseous skeleton. They have an added advantage of being biocompatible and osteoconductive. This in vitro study aims to quantify the drug eluting properties of HA granules by spectrophotometry. Materials and Methods: HA and HASi beads were loaded with gentamicin/ amoxycillin- clavulanate/ vancomycin and grouped into 5. Drug elution was evaluated by means of UV spectrophotometry. Results: Drug eluent levels were well above bactericidal levels in all 5 groups. Conclusion: HA and HASi are viable options for clinicians for targeted drug delivery.